Strategi Public Relations Masjid Ubudiyah Aulawiyah PTPN II Tanjung Morawa dalam Menjaga Current Image Jamaah - Reza, Muhammad; Azhar, Anang Anas (PRoMEDIA, 2023)
Abstract The Public Relations Strategy of Ubudiyah Aulawiyah Mosque PTPN II Tanjung Morawa in maintaining the Current Image of the Jamah is very important for the pilgrims and the people of Tanjung Morawa District. Because that way it can provide positive value for the mosque and also have a positive impact. The subject of how the Public Relations Strategy of the Aulawiyah Ubudiyah Mosque PTPN II Tanjung Morawa contributes to maintaining the image of existing worshippers will be examined in this study with the aim of providing a response through the process of planning, implementation, and assessment. At this time, it is very important for the congregation and people living in Tanjung Morawa District that the Ubudiyah Aulawiyah Mosque PTPN II Tanjung Morawa maintains an effective public relations strategy to maintain the image of the congregation. This descriptive qualitative research method was used for this study. Interviews and observations are the two main ways of data collection in this investigation. After collecting the data, sociological methods are taken to study it in order to better understand the phenomena occurring in the area. The theory developed by Frank Jefkins was used in this investigation. Jefkins' theory consists of five different public relations images, one of which is the image of the company. The findings of the research on the Public Relations Strategy of Ubudiyah Aulawiyah Mosque PTPN II Tanjung Morawa in maintaining the current image of worshippers are in accordance with the theory used, which includes the use of several strategies, namely Social Media (WhatsApp and Facebook), Television, and other media such as Banners, Billboards, and Posters.Keywords: Public Relations, Mosque, Current Image Abstraksi Strategi Public Relations Masjid Ubudiyah Aulawiyah PTPN II Tanjung Morawa dalam menjaga Current Image Jamah sangat penting sekali bagi para jamaah dan masyarakat Kecamatan Tanjung Morawa. Karena dengan begitu dapat meberikan nilai positif bagi masjid dan juga memberikan dampak yang positif. Subjek bagaimana Strategi Humas Masjid Aulawiyah Ubudiyah PTPN II Tanjung Morawa berkontribusi dalam mempertahankan citra jamaah yang ada akan diteliti dalam penelitian ini dengan tujuan memberikan respon melalui proses perencanaan, pelaksanaan, dan penilaian. Pada saat ini, sangat penting bagi jemaah dan orang-orang yang tinggal di Distrik Tanjung Morawa bahwa Masjid Ubudiyah Aulawiyah PTPN II Tanjung Morawa mempertahankan strategi hubungan masyarakat yang efektif untuk menjaga citra Jemaah. Metode penelitian kualitatif deskriptif inilah yang digunakan untuk penelitian ini. Wawancara dan observasi adalah dua cara utama pengumpulan data dalam penyelidikan ini. Setelah mengumpulkan data, metode sosiologis diambil untuk mempelajarinya untuk lebih memahami fenomena yang terjadi di daerah tersebut. Teori yang dikembangkan oleh Frank Jefkins digunakan dalam penyelidikan ini. Teori Jefkins terdiri dari lima gambar hubungan masyarakat yang berbeda, salah satunya adalah citra perusahaan. Temuan penelitian tentang Strategi Humas Masjid Ubudiyah Aulawiyah PTPN II Tanjung Morawa dalam menjaga citra jamaah saat ini sesuai dengan teori yang digunakan, yang meliputi penggunaan beberapa strategi, yaitu Media Sosial (WhatsApp dan Facebook), Televisi, dan media lainnya seperti Spanduk, Baliho, dan Poster.Kata Kunci: Public Relations, Masjid, Current Image